Community involvement in DOT: an innovative kind of care to tuberculosis patient in São Paulo State, Brazil - Arcencio, Ricardo Alexandre; Oliveira, Mayra Fernanda; Villa, Tereza Cristina Scatena (Revista de Enfermagem UFPE on line, 2010)
Abstract Objective: assessing the TB control program coordinators perspective about the community involvement in TB care in priority cities of São Paulo State. Methodology: this is about a semi-structured interviews with 22 subjects. Data were submitted to categorical thematic content analysis. A scale of involvement of community was defined to the study: zero when the subjects did not include the community in TB care; 1, the coordinators involved the community as substitute of human resources; 2: they involved the community to increase the adherence; 3, the coordinators involved the community members to their empowerment. The Research Ethical Committee of Ribeirão Preto Nursing College approved this study (protocol 169/2005) Results: the most coordinators did not achieve satisfactory level of community involvement, they refusal the inclusion of voluntaries in TB facilities. Conclusion: The involvement of community into empowerment perspective is low in state, however in cities where this was employed, the health staffs had obtained increase of adherence, social-mobilization and reduction in preconception and stigma for TB. Descriptors: tuberculosis; consumer participation; health services accessibility; directly observed therapy; primary health care. Resumo Objetivo: analisar a percepção dos coordenadores municipais do Programa de Controle da Tuberculose sobre o envolvimento da comunidade no DOT Metodologia: foram realizadas entrevistas semi-estruturadas com 22 coordenadores. Os dados foram submetidos à análise de conteúdo modalidade temática. Os pesquisadores defiram escala para o envolvimento da comunidade; sendo zero, quando não incluísse a comunidade; um, em substituição ou suprimento de recursos humanos; dois, quando os coordenadores apresentavam como meta a adesão do paciente e três, na perspectiva do “empowerment”. A pesquisa foi aprovada pelo Comitê de Ética em Pesquisa da Escola de Enfermagem de Ribeirão Preto/USP (protocolo 169/2005). Resultados: a maioria dos coordenadores se enquadra na categoria zero, não considerando o envolvimento da comunidade na atenção à TB. Conclusão: o envolvimento da comunidade na perspectiva do empowerment é baixa no Estado de São Paulo, todavia nos locais onde foi implantado, conseguiu-se aumento da adesão, mobilização social e redução do estigma e preconceito relacionados a TB. Descritores: tuberculose; participação comunitária; acesso aos serviços de Saúde; terapia diretamente observada; atenção primária à saúde. RESUMEN Objetivo: analizar la percepción de los coordinadores municipales del Programa de Control de la Tuberculosis sobre la participación de la comunidad en controle de la TB. Metodología: todas las entrevistas estructuradas se llevaron a cabo con 22 sujetos. Los datos fueron sometidos a análisis de contenido, modalidad temática. Los investigadores se remiten al ámbito de la participación comunitaria, siendo cero, aunque no contiene la comunidad, uno en reemplazar mano de obra, y dos, cuando los coordinadores tuvieron la meta de adhesión y tres desde la perspectiva de lo empoderamiento. El estudio fue aprobado por la Ética en la Investigación de la Escuela de Enfermería de Ribeirão Preto - USP (protocolo 169/2005). Resultados: la mayoría de los sujetos cae en categoría de cero, no considerando la participación de la comunidad. Conclusión: La participación de la comunidad en la perspectiva de empoderamiento y baja en el Estado, pero en los lugares donde fue implementada, hemos podido aumentar la adherencia, movilizaciones sociales e reducir el estigma relacionado con la molestia. Descriptores: tuberculosis; participación comunitaria; accesibilidad a los servicios de salud; terapia por observación directa; atención primaria de salud.